PENERAPAN ONLINE SERVICE PEKERJA MIGRAN INDONESIA PADA PT INTAN AYU LESTARI KARAWANG - Ade Rahmat; Nicodias Palasara - Universitas Nusa Mandiri (Indonesian Journal of Networking and Security (IJNS), 2022)
Abstract- The Indonesian Migrant Workers (PMI) complaint system which still uses the manual method, namely by migrant workers reporting complaints by whatsapp or telephone is considered less effective. Moreover, the Admin does not document it computerized so that incoming complaints are not optimal in handling. Complaints facilities and services in the form of a web are expected to overcome current problems. Good service will have a positive effect on the company and increase the trust of service users. The Online Service Information System Of Indonesian Migrant Workers Of PT. Intan Ayu Lestari Karawang is designed in line with the company's policy, which is committed to providing services by increasing customer satisfaction through the company's continuous system improvement program and can be a solution for companies in handling complaints of migrant workers. The waterfall modeling method is applied in system design where the process will be carried out sequentially to ensure the system runs according to plan and is feasible to use and easy to maintain. The results of the development of this system have been connected to the internet, users can access it anytime and anywhere. Keywords: System, Indonesian Migrant Workers, Waterfall Modelling Abstrak- Sistem pengaduan Pekerja Migran Indonesia (PMI) yang masih menggunakan cara manual yaitu dengan pekerja migran melaporkan pengaduan dengan whatsapp atau telepon dianggap kurang efektif. Terlebih Admin tidak mendokumentasikannya secara terkomputerisasi sehingga pengaduan yang masuk menjadi tidak optimal dalam penanganannya. Fasilitas dan pelayanan pengaduan berupa web diharapkan dapat mengatasi permasalahan yang ada saat ini. Pelayanan yang baik akan memberikan efek positif pada perusahaan dan meningkatkan kepercayaan pengguna jasa. Sistem Informasi Online Service Pekerja Migran Indonesia Pada PT. Intan Ayu Lestari Karawang dirancang sejalan dengan kebijakan perusahaan yaitu berkomitmen untuk menyediakan jasa dengan meningkatkan kepuasan pelanggan melalui program peningkatan sistem perusahaan secara berkelanjutan serta dapat menjadi solusi bagi perusahaan dalam menangani pengaduan pekerja migran. Metode watefall modelling diterapkan dalam rancangan sistem dimana proses akan dilakukan secara berurutan untuk memastikan sistem berjalan sesuai dengan rencana dan layak untuk digunakan serta mudah dalam perawatannya. Hasil dari pengembangan sistem ini telah terhubung dengan internet sehingga user dapat mengaksesnya kapanpun dan dimanapun. Kata kunci: Sistem, Pekerja Migran Indonesia, Waterfall Modelling